Designing Strategies and Green Business Models in the Coconut Oil Industry - Abidin Abidin (Fakultas Bisnis, 2021)
As a tropical country, Indonesia has enormous potential for the development of an industry with raw materials from coconut. One of the products that can be developed from coconut is coconut oil. The purpose of this research is to create a strategy and green business model in the medium coconut oil industry (klentik) by utilizing the waste it produces into a variety of prospective products with added value. Various prospective and value added products can be developed from coir, shell, coconut water, dregs, and blondo which are byproducts or waste from the coconut oil production process. The implementation of green business strategies and models has an impact on the sustainability of the medium-sized coconut oil industry, both in terms of profitability, social and environmental aspects.